Evaluating the impact of local alcohol licensing decisions on outcomes for the community: a systematic review - Elizabeth Goyder; Mark Clowes; Lindsay Blank; Emma Hock; Marie Rogerson (BMJ Public Health)
Background International evidence reviews suggest that reducing the availability of alcohol positively impacts both levels of alcohol consumption and associated harms. To understand the impact of recent changes to alcohol licensing and public health in the UK, this review aimed to identify and synthesise quantitative research evidence on the impact of local alcohol licensing decisions on the health and well-being of the community.Methods We searched peer-reviewed articles and grey literature for UK studies. We extracted and tabulated key data from the included papers and appraised study quality. We included topic expert and public consultation to confirm the scope of the evidence synthesis and suggest evidence for inclusion. We synthesised narratively and made recommendations based on our findings.Results We identified a small volume (seven papers) of evidence regarding the health (and related) impacts of local alcohol licensing decision undertaken in the UK local authorities. The evidence we identified did not demonstrate a consistent or sustained association between local interventions and health or crime outcomes downstream. This was despite relatively sophisticated study designs using a range of available data sources and some longer-term analysis.Conclusion Given that the impacts of local licensing decisions are currently limited, greater regulatory powers are needed if local licensing interventions are to be an effective public health interventions to reduce alcohol-related harms.